ANALISIS KONTRUKSI PEMAKNAAN TRADISI TABUIK (STUDI PETER L. BERGER DI PARIAMAN) - Zike Martha; Salsabila Intania; M.A Dalmenda; Tri Sukma; Azizah Putri (Smart Education, 2026)
Abstract: This study aims to analyze the social construction of meaning surrounding the Tabuik tradition in Pariaman City through the perspective of Peter L. Berger’s Social Construction of Reality theory. The Tabuik tradition has undergone a shift in meaning, situated between the preservation of cultural values, the pressures of tourism commodity, and resistance emerging from religious discourse. This research employed a qualitative method with a phenomenological approach. Data were collected through in-depth interviews with key informants, including traditional leaders (Tuo Tabuik), as well as supporting informants from students of the Minangkabau Literature Program, who represented the younger generation. Data analysis was conducted through the stages of data collection, data presentation, and conclusion drawing. The findings reveal that the construction of meaning of the Tabuik tradition among students is shaped through the integration of empirical experiences, formal education, and social interactions. Theoretically, these meanings are manifested in three major dimensions: cultural identity, spiritual experience, and cultural transformation in the modern era. The study indicates that students perceive Tabuik from two contrasting perspectives. On the one hand, it is regarded as a symbol of ancestral heritage preservation that embodies important philosophical and cultural values. On the other hand, concerns emerge regarding its transformation into a tourism commodity, which may reduce the sacredness of the tradition. Furthermore, the influence of social media and Generation Z lifestyles has encouraged the reinterpretation of Tabuik as a medium for self-expression and social existence. Therefore, this study confirms that the meaning of the Tabuik tradition is dynamic and continuously evolving in response to social influences and the communication patterns of younger generations. Keywords: Social Construction; Peter L. Berger; Tabuik Tradition; Pariaman; Phenomenology. Abstrak: Penelitian ini bertujuan untuk menganalisis secara mendalam konstruksi sosial pemaknaan tradisi Tabuik di Kota Pariaman dengan menggunakan analisis Teori Konstruksi Sosial atas Realitas dari Peter L. Berger. Tradisi Tabuik saat ini mengalami pergeseran makna antara pelestarian nilai kultural, desakan komoditas pariwisata, dan resistensi dari diskursus keagamaan. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi, data dikumpulkan melalui wawancara mendalam terhadap informan kunci yang terdiri dari tokoh adat (Tuokan Tabuik) serta informan pendukung dari kalangan mahasiswa Prodi Sastra Minangkabau sebagai representasi generasi muda. Analisis data dilakukan melalui tahapan pengumpulan data, penyajian data, dan penarikan kesimpulan. Penelitian ini mengungkapkan bahwa konstruksi makna tradisi Tabuik di kalangan mahasiswa terbentuk melalui integrasi pengalaman empiris, pendidikan formal, dan interaksi sosial. Secara teoretis, makna tersebut terbagi ke dalam dimensi identitas budaya, pengalaman spiritual, serta transformasi budaya di era modern. Hasil studi menunjukkan persepsi mahasiswa: di satu sisi, Tabuik dipandang sebagai simbol pelestarian warisan leluhur yang bernilai filosofis, namun di sisi lain, terdapat kekhawatiran akan pergeseran maknanya menjadi sekadar komoditas pariwisata yang mereduksi kesakralan tradisi. Lebih lanjut, pengaruh media sosial dan gaya hidup generasi Z turut mendorong reinterpretasi tradisi sebagai bentuk eksistensi diri. Dengan demikian, penelitian ini menegaskan bahwa makna tradisi Tabuik bersifat dinamis dan terus berkembang seiring dengan pengaruh sosial serta pola komunikasi generasi muda. Kata kunci: konstruksi sosial; Peter L. Berger; tradisi tabuik; Pariaman; fenomenologi.